History and Development of the Benjang Wrestling Organization in Ujungberung in 2000-2021 - HAMID, Helmi Abdul; HIDAYAT, Asep Achmad; LESTARI, Fathia (PT. Keberlanjutan Strategis Indonesia, 2023)
Purpose: The art of benjang wrestling has long lived and developed among the people of East Bandung from 1965-1970. The benjang wrestling arts organization was formed to accommodate and provide facilities for activists and actors who are involved in the world of benjang wrestling arts, especially for benjang athletes, to continue to preserve the benjang wrestling arts and regenerate benjang athletes so that they continue to exist.Methodology: This research uses the historical method, which consists of four stages, namely heuristics (source gathering), criticism (data selection), interpretation (data interpretation), and historiography (history writing).Findings:Based on the results of the research that has been done, it can be concluded that the Benjang Wrestling Arts Organization in Ujungberung in 2000-2021 is a Benjang wrestling arts organization that was formed to become a place or place for activists and actors who participate in the benjang wrestling arts. This organization was initially formed from a Paguyuban in 2000 and developed into an organization in 2015. The purpose of establishing this organization is to maintain and preserve the art of benjang wrestling to preserve it to the times and to contribute to always trying to regenerate the following benjang athletes. So that there will be a successor.Implication:With the regeneration carried out by the Benjang Wrestling Arts organization, successors will continue to emerge who can contribute and provide achievements for the Benjang Wrestling Arts so that this art will continue to exist and be maintained for the next generation.